2010
DOI: 10.1111/j.1538-7836.2009.03653.x
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein Ibα–von Willebrand factor interaction induces platelet apoptosis

Abstract: Summary. Background: The interaction of glycoprotein (GP) Iba with von Willebrand factor (VWF) initiates platelet adhesion, and simultaneously triggers intracellular signaling cascades leading to platelet aggregation and thrombus formation. Some of the signaling events are similar to those occurring during apoptosis, however, it is still unclear whether platelet apoptosis is induced by the GPIba-VWF interaction. Objectives: To investigate whether the GPIba-VWF interaction induces platelet apoptosis and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 32 publications
4
86
1
Order By: Relevance
“…Next, we investigated the role of PKA in platelet apoptosis. As previously reported, platelet apoptosis is a mitochondria-mediated intrinsic form of programmed cell death (6,7). Upon apoptotic stimulation, BCL-2 family proteins interact with the mitochondrial outer membrane, leading to transmembrane potential (ΔΨ m ) depolarization as well as activation of caspases (27,28).…”
Section: 0mentioning
confidence: 90%
See 1 more Smart Citation
“…Next, we investigated the role of PKA in platelet apoptosis. As previously reported, platelet apoptosis is a mitochondria-mediated intrinsic form of programmed cell death (6,7). Upon apoptotic stimulation, BCL-2 family proteins interact with the mitochondrial outer membrane, leading to transmembrane potential (ΔΨ m ) depolarization as well as activation of caspases (27,28).…”
Section: 0mentioning
confidence: 90%
“…Accumulating evidence indicates that the intrinsic program for apoptosis results in platelet destruction under pathological and physiological conditions (6,7). Similarly to eukaryotic cells, BAK and BAX are the 2 fated killers for those platelets that are not consumed during thrombosis and hemostasis (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The Hb-GP1bα interaction stimulated the intrinsic (mitochondria-dependent) pathway of apoptotic signals (Figure 4), as other studies have demonstrated for VWF-GP1bα interactionmediated apoptosis in platelets. 33,34 In fact, the Hb-GP1bα interactions stimulated the activation of proapoptotic proteins Bak and Bax, release of apoptogenic cytochrome c from mitochondrial intermembrane space to the cytosol, and the activation of caspase-9 and caspase-3 ( Figure 4B and Online Supplementary Figure S10). The Hb-mediated apoptotic responses in turn induced the cytoskeleton expression of PS in platelets ( Figure 4A) and generation of platelet microparticles ( Figure 1C) as described in other agonists (such as thrombin, collagen, or ristocetin) that induced signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, the GPIb/IX complex, through its association with the signaling protein 14-3-3, has been implicated in the induction of platelet apoptosis on VWF binding. 30 An analogous process may account for the induction of apoptosis in Mks on association of QITP antibodies with the GPIb/IX complex.…”
Section: Discussionmentioning
confidence: 99%